Vpliv tumorske mase na učinek zdravljenja z virusom newcastleske bolezni - Godić, Aleksandar (Medicinski razgledi, 2001)
Newcastle disease virus (NDV) has been shown to have an inhibitory influence on tumor growth in various experimental conditions. We studied the effect of daily applicatipn of a wild strain of NDV (NDV w.s:) and the effect of tumor mass on therapy with NDV w.s. in mice with intraperitoneally transplanted Ehrlich ascites tumor (i.p. EAT). 117 mice of CBA/H strain were used. They were divided into three groups: in the first one, therapy was started 1 week after tumor transplantation, in the second 2 weeks and in the third 3 weeks after tumor transplantation. The mice in experimental groups were treated withi.p. NDV w.s., and those in control groups with i.p. physiological saline.The virus was applied daily until the end of the experiment. The lengthof survival, number of metastases (macro and microscopically) end frequency.of ascites and tumor in the region of EAT transplantation were measured. The length of survival in experimental groups was prolonged, but theprolongation was significant only in the second group. The number of metastases was proportional to the length of survival. The frequency of ascites in experimental groups was lower. Tumor mass at the beginning of therapy had no significant effect on virus therapy. Only a lower frequency of ascites in the third group and an increasing frequency of tumors in the regionof i.p. EAT injection from the first to the third group were found. The daily application of NDV w.s. in mice with i.p. EAT was shown to prolong survival of the animals; it also lowered the frequency of ascites, but had no effect on the number of metastases. Initial tumor mass had no significant influence on therapy with NDV w.s.
Keywords: Carcinoma, ehrlich tumor; Karcinom, Ehrlichov tumor; Newcastle disease virus; Novotvorba, metastaza; Analiza preživetja; Neoplasm metastasis; Miši seva CBA; Mice, inbred cba; neoplasm; Survival analysis; tumor; therapy; Paramyxovirinae; zdravljenje; virus Newcastle; miši; preživetje